The future of doping control in athletes. Issues related to blood sampling - Birkeland, K. I.; Hemmersbach, P. (Sports Medicine, 1999)
When current antidoping programmes were developed, the most frequently used doping agents were xenobiotics, such as stimulants and anabolic steroids, that are readily detectable in urine with the use of gas chromatography and mass spectrometry. As control of traditional doping agents became effective, some athletes turned to other means to improve performance, including blood doping and the application of recombinant peptide hormones such as erythropoietin and growth hormone. Doping with these agents is not easily detected in urine samples, and therefore new strategies must be developed as a supplement to those already in use. Such strategies will probably include analysing blood samples, as several of the most promising methods that are able to detect modern doping agents use blood as the analytical matrix. Non-autologous blood doping results in an admixture of self and foreign red blood cells that can be detected in a blood sample with the methods available. Methods to indicate doping with erythropoietin include the indirect finding of an elevated level of soluble transferrin receptor in serum, or a direct demonstration of a shift from the normal to an abnormal spectrum of erythropoietin isoforms. To indicate doping with growth hormone, a set of serum parameters including insulin growth factors and their binding proteins are under investigation as indirect evidence. A direct method using isotopic differences between endogenous and recombinant growth hormones is being investigated. A similar method has been established to detect the administration of testosterone esters. Several legal and ethical questions must be solved before blood sampling can become a part of routine doping control, but the major ethical question is whether sport can continue as today without proper methods to detect many modern doping agents.